An introduction to survey research - Cowles, Ernest L.; Nelson, Edward (Quantitative approaches to decision making collection., 2015)
This book is an introduction to survey research for those who want an overview of the survey process. It is intended to describe fundamental survey components to help both students and managers understand and use surveys effectively and avoid the pitfalls stemming from bad survey construction and inappropriate methods. We begin by talking about how best to identify the information needed and the best approach to get that information. We then discuss the processes commonly involved in conducting a survey including the value of both obtaining a representative sample and dealing with the types of errors that can distort results. Next, each chapter focuses on one of the key components of constructing and carrying out a survey, including the elements to consider when developing a survey, the modes of survey delivery, writing good questions, conducting the survey, and presenting the results. Each chapter concludes with a summary of important points contained in the chapter and an annotated set of references indicating where readers can go for more information on chapter topics.